"But it wasn't really cheating": Dark Triad traits and perceptions of infidelity. (February 2023) - Brewer, Gayle; Guothova, Alexandra; Tsivilis, Dimitris
Abstract: Infidelity constitutes a threat to those in exclusive romantic relationships and may lead to relationship dissolution. There is, however, substantial variation with regards to the acts that are or are not considered to be infidelity. In the present study, we investigate the relationship between Dark Triad traits and the acts perceived to constitute infidelity. Five categories of infidelity are considered; online infidelity, fantasized infidelity, emotional infidelity, sexual infidelity, and hidden attachment. Dark Triad traits (Machiavellianism and primary psychopathy) predicted the extent to which specific acts were perceived to constitute infidelity when controlling for demographic factors and personal experience of infidelity. In particular, those high on Machiavellianism were less likely to perceive fantasizing and expressed emotion as infidelity. Those high on primary psychopathy were more likely to perceive fantasizing and emotional expression as infidelity and less likely to consider sexual acts or hidden attachment as indicators of infidelity. Highlights: We investigated perceptions of infidelity. Machiavellianism and psychopathy but not narcissism predicted perceived infidelity Personal experience of infidelity also predicted perceptions of such behaviour.